Recycling of Mixed Plastics Waste Containing Polyethylene, Polyvinylchloride and Polyethylene Terephthalate (Chemical Engineering Research Bulletin, 2013)
This research work was undertaken to investigate the spectroscopic, morphological and rheological properties of polymer blends made of recycled Polyethylene terephthalate (PET), Polyethylene (PE) and Polyvinylchloride (PVC). Different blends of these polymers were made by varying composition of PET. Each recycled blend consisted of recycled polymers and ethylene propylene diene monomer (EPDM) as a compatiblizer. Spectroscopic and morphological characteristics of recycled polymer blends were investigated using Fourier Transform Infrared Spectrometer (FTIR) and Scanning Electron Microscope (SEM) respectively. SEM analysis revealed low miscibility among these three polymers. While rheological properties were investigated using Melt Flow Indexer (MFI). The rheological characterization indicated that melt flow index (MFI) decreases with increase of PET concentration in PE/PET/PVC recycled blends. It was also observed that with increase of PET contents recycled blends show pseudoplastic behavior. DOI: http://dx.doi.org/10.3329/cerb.v16i1.17471 Chemical Engineering Research Bulletin 16(2013) 25-32